Cosmetic Products and Industry - New Advances and Applications 2023
DOI: 10.5772/intechopen.109809
|View full text |Cite
|
Sign up to set email alerts
|

The Beauty and the Toxic Beast: Use of Comet Assay to Study Antigenotoxicity of Natural Ingredients

Abstract: The natural cosmetics market has grown since consumers became conscious of natural-based ingredients. A significant number of cosmetics have noxious and chemically potent substances. Thus, the use of natural and organic cosmetics has become increasingly important. An intense investigation into the benefits fruits and plants can bring to our health is required. A healthy lifestyle can reduce these problems, including the consumption or use of substances that protect the genome through various mechanisms that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…Further research is warranted to unravel the precise molecular mechanisms through which oleic acid confers its protective effects on DNA integrity and to explore its potential therapeutic applications in preventing diseases related to DNA damage. The results obtained with olive oil treatment closely align with findings from a previous study, indicating consistent outcomes across independent investigations [26].…”
Section: Discussionsupporting
confidence: 89%
“…Further research is warranted to unravel the precise molecular mechanisms through which oleic acid confers its protective effects on DNA integrity and to explore its potential therapeutic applications in preventing diseases related to DNA damage. The results obtained with olive oil treatment closely align with findings from a previous study, indicating consistent outcomes across independent investigations [26].…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the successful preparation of the olive tree leaf tincture, it is important to note that olive tree leaves have been reported to possess antigenotoxicological properties. Several studies have indicated that extracts derived from olive tree leaves exhibit potential protective effects against DNA damage and oxidative stress [18]. The inclusion of olive tree leaves in the tincture formulation suggests the possibility of harnessing these antigenotoxicological properties for potential therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%